Phytate degradation and phosphorus utilisation by broiler chickens fed diets containing wheat with increased phytase activity. Issue 3 (4th May 2022) - Papp, M.; Sommerfeld, V.; Schollenberger, M.; Avenhaus, U.; Rodehutscord, M.
ABSTRACT: 1. The objective of this study was to investigate wheat genotypes bred for increased intrinsic phytase activity for InsP6 disappearance and the formation of lower inositol phosphates in such wheat-fed broiler chickens. The influence of monocalcium phosphate (MCP) supplementation on these characteristics and the utilisation of P and Ca were also determined. A three-step in vitro assay and a broiler trial were performed. 2. In the 63 wheat genotypes tested in vitro, phytase activity varied from 1900 FTU/kg to 5200 FTU/kg, and InsP6 disappearance increased with higher phytase activity of wheat in a linear manner. The addition of MCP significantly reduced in vitro InsP6 disappearance by one-third, independent of the inclusion level of wheat in the feed. When exogenous phytase was added to wheat, in vitro InsP6 disappearance increased independently of the phytase activity of the wheat used. 3. In the broiler trial, four wheat genotypes with phytase activities between 2400 and 3700 FTU/kg were included at 400 g/kg in diets with and without MCP. The diets were not pelleted. Separately, wheat 1, without MCP, was tested with the addition of exogenous phytase. Unsexed Ross 308 broiler chickens were allocated to 72 metabolic units of 10 birds each and assigned one of the nine diets. Mineral utilisation was measured based on excreta collection from 20 to 23 d of age. Digesta from the crop and terminal ileum were collected on d 24. 4. In the crop and ileum, InsP6 disappearance was not affected by the wheat genotypes, but the addition of MCP significantly decreased InsP6 disappearance. Precaecal P disappearance was significantly reduced by the addition of MCP, with wheat genotypes also exerting an effect. Wheat genotypes and the addition of exogenous phytase significantly affected P utilisation. Exogenous phytase had no effect on InsP6 disappearance in the crop but did up to the terminal ileum, the precaecal InsP6 and P disappearance increased with the addition of exogenous phytase. 5. Although the intrinsic wheat phytase activity exerted distinct effects on in vitro InsP6 disappearance, no such effect was found in the broiler trial. The addition of MCP significantly inhibited InsP6 degradation in vitro and in vivo .